Kontribusi Perempuan Bali dalam Pengembangan Pariwisata Kreatif di Ubud - Ni Made Prasiwi Bestari; Ni Wayan Widhiasthini (Jurnal Kajian Bali (Journal of Bali Studies), 2023)
The swift growth and intense competition in the tourism industry have driven Ubud to constantly innovate and devise creative forms of tourism that enhance its appeal to visitors. This article examines and assesses the contributions of women in the advancement and diversification of creative tourism in Ubud. This case studies research employs qualitative methodologies, involving the collection of data through various means, including direct observation, structured interviews, netnography, and comprehensive document analysis. The article concludes Balinese women have contributed significant effort in creating creative tourism in Ubud as can be seen in cooking class. This study also finds how Balinese women transform their role from being worker into entrepreneur in the field of creative tourism in Ubud.